Aflatoxin contamination in different varieties of peanuts - and H.C. DUBE2, R.J. VERMA1, A.S. KOLHE1 (Indian Phytopathology, 2002)
Eight groundnut varieties, (Dhokya Red, Dhokya White, Ghungari Simple, G-2, G-51, HB-11, G-97 and Akola Farm) were screened for aflatoxinogenic fungi and aflatoxin contamination in Maharashtra, India. Of the 71 A. flavus isolates tested, 34 producedaflatoxin in SMKY liquid medium and the majority of those produced B1 type aflatoxins. It is concluded that the ability of isolates to produce toxins and the type of toxin produced is due to genetic factors.